FRI0572-HPR Kinesiophobia Affects Early Stage Functional Levels after Total Knee Arthroplasty. (10th June 2014) - Guney, H.; Kinikli, G.I.; Caglar, O.; Yuksel, I.
Abstract : Background: Though total knee arthroplasty (TKA) is a successful procedure for the late stage of knee osteoarthritis, high pain levels and functional impairment are considerable. In addition, TKA patients suffer from psychological symptoms such as kinesiophobia and fear of motion. Objectives: The purpose of this study was to determine the fear of motion and kinesiophobia impact on early functional capacity and performance. Methods: Forty-six patients who underwent unilateral TKA were included in the study. Tampa Scale for Kinesiophobia (TSK) was applied to detect kinesiophobia. A high value on the TSK indicates a high degree of kinesiophobia and a score of 37 differentiates between high and low scores. Patients were divided into two groups either to have high scores (Group I; high kinesiophobia, n=22) or low scores (Group II; low kinesiophobia, n=24). Timed up and go (TUG) and 2-minute walk tests (2-MWT) were used to determine the early stage of functional status. Intensity of pain was measured with visual analog scale (VAS). Knee flexion range of motion (ROM) and day of hospital stay were recorded. Assessments were applied on the post-operative day four. Statistical analysis of the data was performed with Mann-Whitney U test Results: There were no differences in age (z= -0.320, p=0.749), BMI (z= -0.299, p=0.765) and hospital stay (z= -0.798, p=0.425) between Group I (mean age = 64.1±5.1 years) and Group II (years mean age = 63.5±5.3 years) (Table 1 ). The pain levels (z= -0.115, p=0.909) and knee flexion ROM (z= -0.088, p=0.930) were similar between groups. While there was no difference in TUG test (z= -0.416, p=0.676) there was significant difference in 2-MWT (z= -4.788, p<0.001). Group II (low kinesiophobia) had better 2-MWT results compared to Group I (high kinesiophobia) (Table 1 ). Conclusions: Kinesiophobia and fear of motion have an adverse effect on early stage walking performance in TKA patients. References: Monticone M, Ferrante S, Rocca B, Salvaderi S, Fiorentini R, Restelli M, Foti C. Home-based functional exercises aimed at managing kinesiophobia contribute to improving disability and quality of life of patients undergoing total knee arthroplasty: a randomized controlled trial. Arch Phys Med Rehabil. 2013 Feb;94(2):231-9. Singh JA, Lewallen DG. Patient-level improvements in pain and activities of daily living after total knee arthroplasty.Rheumatology (Oxford). 2014 Feb;53(2):313-20. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4248